Motor coordination of eye-foot and ear-foot in adolescents: a comparison between adolescents engaged in rhythmic sports and ball sports - Trongjitpituk, Ravisara (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Purpose. Motor coordination is essential for physical fitness and effective participation in sports. Various sports emphasise different types of coordination, with rhythmic sports focusing on timing and synchronisation and ball sports on quick reactions and precision. This study examines the impact of participation in rhythmic and ball sports on eye-foot and ear-foot coordination in adolescents.Methods. Sixty adolescents (30 boys, 30 girls; mean age 12.95 ± 0.12 years) were divided into three groups: rhythmic sports, ball sports, and inactive, with 20 participants in each group. Eye-foot coordination was measured using a reaction time test, and ear-foot coordination was assessed by the coefficient of variation (CV) of inter-tap intervals (ITI). Data were analysed using one-way ANOVAs and post-hoc Bonferroni tests to compare the coordination skills among the three groups.Results. The ball sports group demonstrated significantly better eye-foot coordination compared to both the rhythmic sports (p = 0.028) and inactive groups (p < 0.001). Additionally, the rhythmic sports group outperformed the inactive group in eye-foot coordination (p = 0.021). For ear-foot coordination, the rhythmic sports group showed greater timing consistency (lower CVITI) than both the ball sports (p = 0.012) and inactive groups (p = 0.034). These findings indicate the specific benefits of different types of sports training on motor coordination in adolescents.Conclusions. Adolescents in ball sports show better eye-foot coordination, while those in rhythmic sports excel in ear-foot coordination. Sport-specific training significantly enhances these motor skills, indicating the need for tailored training programs to optimise adolescent development.
Keywords: motor coordination; eye-foot coordination; ear-foot coordination; rhythmic sport; ball sport